The efficacy of acupuncture for trigeminal neuralgia: an overview of systematic reviews - He, Hong-xian; Li, Ya-xin; Xiao, Ya-song; Fan, Wen-hui; Xue, Hua (Frontiers in Neurology, 2024)
Background Many systematic reviews (SRs) and meta-analysis (MAs) have reported the efficacy of acupuncture treatment for primary trigeminal neuralgia (PTN), but the quality of evidence is unknown and therefore needs to be evaluated comprehensively. Methods Eight electronic databases were searched from their inception until January 5, 2024. The methodological quality, reporting quality, and risk of bias of the included SRs were assessed by the assessment of multiple systematic reviews 2 (AMSTAR-2), the Risk of Bias in Systematic Reviews (ROBIS) tool, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The quality of evidence for outcome measures was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Results We identified 13 SRs/MAs met inclusion criteria. According to the results of the AMSTAR-2, six were rated as critically low quality and seven as low quality. According to ROBIS assessment, 8 SRs/MAs were classified as low risk, and 5 SRs/MAs were found to be high risk. The PRISMA report still has some reporting deficiencies in aspects such as protocol and registration, search strategy, risk of bias, additional analyzes and funding. According to the GRADE system, no high-quality evidence was found, 1 was of moderate quality, 4 were of low quality, and 8 were of critical low quality. Conclusion Based on the evidence collected, acupuncture shows promise as a treatment for PTN patients. However, it is important to note that the included SRs/MAs generally have low methodological quality and evidence quality. Therefore, caution must be exercised when interpreting this conclusion. To enhance future research in this area, it is recommended to adequately report methodological details and adhere to guidelines for conducting SRs/MAs. Systematic review registration: https://www.crd.york.ac.uk/prospero/, identifier CRD42024499280.